(untitled) (Bangladesh Journal of Botany, 2023)
Variation in the mycelial growth was observed within the isolates of Alternaria brassicae and A. brassicicola on PDA medium. The isolates were also found to differ from each other in respect to cultural and conidial characters. The colonies were cottony or fluffy in appearance with varied colour from olivaceous green, white, off white, light brown to brown. Colony margins were smooth, rough or wavy and zonation was either present or absent. In Alternaria brassicae isolates, conidial length varied from 92.5 to 116.2 μm, conidial width varied from 11.8 to 17.2 μm, horizontal septa varied from 3.4 to 5.3, vertical septa varied from 0.3 to 1.4 μm and beak length varied from 68.4 to 88.4 μm. However, in A. brassicicola isolates, conidial length varied from 46.8 to 52.8 μm, conidial width varied from 12.8 to 14.6 μm, horizontal septa varied from 3.2 to 3.7 and vertical septa varied from 0.2 to 0.8 μm. Beak was absent in the isolates of A. brassicicola. In the isolates of A. brassicae and A. brassicicola, maximum per cent disease intensity and spot size on all the genotypes was observed in Ab11 and Abl2, respectively. Bangladesh J. Bot. 52(2): 331-336, 2023 (June)